Predicted S and s phenotypes from genotyping results among Thai populations to prevent transfusion-induced alloimmunization risks - Oytip Nathalang (2018)
© 2018 Elsevier Ltd Background: S and s antigens of the MNS system are of clinical importance because alloanti-S and -s have usually caused delayed hemolytic transfusion reactions and hemolytic disease of the fetus and newborn. Various red cell genotyping has been established to predict the phenotypes to solve serological test limitations. Objectives and methods: This study aimed to determine S and s genotype frequencies and to estimate the alloimmunization risks among central, northern and southern Thai populations. Altogether, 1237 blood samples from Thai blood donors were included. Only 150 samples were tested with anti-S and anti-s by indirect antiglobulin test. All samples were genotyped for GYPB*S and GYPB*s alleles using inhouse PCR with sequence-specific primer. Additionally, the allele frequencies were used to estimate alloimmunization risks and compare with other populations. Results: The phenotyping and genotyping results in 150 samples were in 100% concordance. The allele frequencies of GYPB*S in central, northern and southern Thais were 0.061, 0.040 and 0.097, and GYPB*s were 0.939, 0.960 and 0.903, respectively. The frequencies among central Thais were similar to those among northern Thai and Korean populations (P > 0.05) but significantly differed from those of Asian, Caucasian African American and Hispanic populations (P < 0.05). In addition, the risk of S alloimmunization among southern Thais (0.1566) was higher than those among central (0.1038) and northern Thais (0.0736). Conclusion: This was the first study to report S and s predicted phenotypes and estimate alloimmunization risks among Thais, which is beneficial to prevent transfusion-induced alloimmunization among donors and patients.